PENAMBAHAN SERBUK LIMBAH BATU KUMBUNG PADA CAMPURAN BETON - M Rifki Andri Saputro; Rasio Hepiyanto (Litbang Pemas - Universitas Islam Lamongan, 2018)
Concrete is the most common construction material in use and demand because it is an easily formed base material with a relatively cheap price compared to other construction. The utilization of waste powder of white brick on the concrete mixture is very useful in terms of environmental insight aspects can reduce pollution of dust in the area where the white brick is produced. In addition, the use of white brick powder can reduce environmental pollution because the dust is a solid material that is not easily soluble and not volatile. This research was done by mixing concrete and powder of white brick waste as cement added material with the composition of 5% and 10%. The highest value of compressive strength of concrete was obtained from the mixture composition of 5% addition of white brick waste which reached the value of 18,20 Mpa at age 28 day. While the mixture composition of 10% decreased the compressive strength of concrete by 16.07%.